Proceedings of 12th World Congress on Genetics Applied to Livestock Production (WCGALP) 2022
DOI: 10.3920/978-90-8686-940-4_523
|View full text |Cite
|
Sign up to set email alerts
|

523. Sequence-based GWAS meta-analyses for beef production traits

Abstract: Five partners of the H2020 BovReg project have performed sequence-based GWAS for 28 beef production traits (4 growth, 9 morphology, and/or 15 carcass traits) using 54,782 animals from 15 different purebred or crossbred cattle populations. These results were herein combined to conduct 16 different meta-analyses (MA) with both the z-score and the fixed effects MA methods. We identified QTL in 15 MA on BTA2,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
1
1
Order By: Relevance
“…RAB2A gene harbors the most signi cant genomic region for body con rmation, the study further reported the genes to have the highest proportion of the total additive genetic variance (3.89%) of body con rmation [28]. [29] reported SLIT2 to be associated with growth and carcass traits Simmental vs Angus, or with a function that may be related to meat production, which was different to our fundings. Tetraspanin 9 (TSPAN9) revealed an association with lactation persistency for Simmental vs Angus, which was consistent with a study by [30] who reported the gene to have an association with lactation persistency in Canadian Holstein.…”
Section: Discussioncontrasting
confidence: 61%
“…RAB2A gene harbors the most signi cant genomic region for body con rmation, the study further reported the genes to have the highest proportion of the total additive genetic variance (3.89%) of body con rmation [28]. [29] reported SLIT2 to be associated with growth and carcass traits Simmental vs Angus, or with a function that may be related to meat production, which was different to our fundings. Tetraspanin 9 (TSPAN9) revealed an association with lactation persistency for Simmental vs Angus, which was consistent with a study by [30] who reported the gene to have an association with lactation persistency in Canadian Holstein.…”
Section: Discussioncontrasting
confidence: 61%
“…The identification of essential genes, haplotypes, and their regulatory mechanisms as markers for quantitative traits has the potential to enhance strategies for selecting beef cattle both currently and in the future [22]. There has been a significant focus on conducting genome-wide association studies (GWAS) to investigate economic traits in cattle, including fertility traits [23][24][25][26][27][28], production traits [29][30][31], somatic cell score [32][33][34][35], and disease resistance [36][37][38][39] in recent years. Numerous significant single nucleotide polymorphisms (SNPs) and biologically relevant genes were identified.…”
Section: Introductionmentioning
confidence: 99%